Pengaruh Model Pembelajaran Kausalitik Terhadap Kemampuan Pemecahan Masalah Fisika Peseta Didik - Sari, Yulyatna; Rokhmat, Joni; Hikmawati, Hikmawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2020)
The effect of causalitic learning model on problem solving ability in Physics students. This study aims to find out the effect of causalitic learning model on problem solving ability in Physics students. The type of research used is quasi-experiment with untreated control group design with pretest and posttest. The population is all class X students of SMAN 1 Narmada, amounting to 396 people. Sampling of research using purposive sampling technique, so that selected X MS 1 as the experimental class and X MS 2 as the control class. The experimental class was treated in the form of a causalytic learning model while the control class was treated in the form of a conventional learning model. The research instrument consisted of a test of problem solving ability by considering the validity, reliability, level of difficulty of the questions and the different power of the questions. KPM Posttest data is tested for normality, then proceed with hypothesis testing using t-test. Hypothesis test results of the calculated t value is greater than the table then Â is accepted. So the causalytic learning model influences the problem solving ability in Physics students.Â Keywords: Causalytic learning model; Solution to problem; Learners